(untitled) (Cultura Económica, 2025)
The objective of this essay is to examine the current relevance of Giambattista Vico’s political philosophy. To this end, I begin by raising the question of the current relevance of a philosophical system in general, and of Vico’s science in particular. I then analyze the meaning Vico assigned to the term "political philosophy." Finally, I draw some conclusions about the relevance of his political philosophy.